Interactive effects of iron and light limitation on the molecular physiology of the Southern Ocean diatom Fragilariopsis kerguelensis - Carly M. Moreno; Weida Gong; Natalie R. Cohen; Kimberly DeLong; Adrian Marchetti (Limnology and Oceanography, 2020)
The polar diatom Fragilariopsis kerguelensis is ubiquitous in Southern Ocean waters and is a major responder to iron fertilization, encountering large gradients in iron concentrations and light availability. We performed a comparative transcriptomic analysis of F. kerguelensis grown under varying iron and light conditions in order to investigate the molecular underpinnings that may explain its physiological response to iron and light limitation. Low iron reduced growth rates more than low light, but there was not an additive effect of low iron and low light on growth rate. Low iron treatments (saturating and low light) had the largest transcriptomic response; however, expression patterns were more similar in low light treatments (high and low iron). Under iron and light limitation, carbon fixation and amino acid, ribosome, and sulfur metabolisms were overrepresented relative to the control (iron replete, saturating light). Transcripts of genes encoding for the proteins aquaporin, proteorhodopsin, plastocyanin, and flavodoxin were overrepresented to the greatest extent in the low iron/low light treatment, indicating there may be an additive effect of iron/light colimitation at the molecular level. Iron and light replete cells demonstrated increased expression of genes encoding for the proteins ferritin, carbonic anhydrase, and numerous iron‐dependent proteins relative to the growth‐limiting treatments. This transcriptome analysis reveals mechanisms that may underpin the ecological success of this diatom in low iron and light environments, highlighting the important role of diversified photosynthetic isoforms, iron acquisition, unique detoxification mechanisms of reactive oxygen species, and metabolic shifts in amino acid recycling and carbon metabolism.